CMOS depth sensor with programmable filter circuits for environment‐adaptive noise suppression. Issue 19 (1st September 2018) - Seo, H.; Kim, B.; Chun, J.‐H.; Kim, S.‐J.; Choi, J.
Abstract : This Letter introduces a CMOS depth sensor with a multi‐resolution single‐photon avalanche diode (SPAD) array and area‐efficient filter circuit with a programmable reference for environment‐adaptive noise suppression. Four SPADs compose a macro‐pixel for detecting targets at a short distance with high resolution, whereas 4 × 4 SPADs are reconfigured to a super‐pixel for a long distance with enhanced signal‐to‐noise ratio. To provide environment‐adaptive noise suppression in the miniaturised SPAD array, an area‐efficient filter circuit with a programmable reference is proposed: a digital macro‐filter corresponding to a macro‐pixel and an analogue super filter corresponding to a super‐pixel. The prototype chip was fabricated with a 110 nm CMOS image‐sensor process, including 128 SPAD farm arrays and 128 analogue front‐end circuits. With high background light of over 90 klx and a high dark‐count rate of over 27.1 kHz, the time‐of‐flight could be measured by filtering out invalid pulses from noise without using multiple time‐to‐digital converters per pixel, which enables the implementation of miniaturised LiDAR‐sensor systems on a chip.